Impact of COVID-19 Pandemic on Stock Market Returns - Madai, Tek Bahadur (KMC Journal, 2023)
This study examines how COVID-19 epidemic has affected stock returns. A causal-comparative design of quantitative research is used to examine how daily COVID-19 infection and fatality cases affect stock market performance. The analysis found that changes in the daily rate of new infections have had a substantial influence on overall equities returns as well as cross-over stock markets. In contrast, it was found that COVID-19 related deaths had a negative but often insignificant effect. The categorical variable magnitude of the influence on the equity market was determined to be relatively little. With the use of a time series graph and a regression model, the empirical data was examined. The time frame for the study was 100 days from the discovery of COVID-19 cases in the tested countries in 30 countries. The results of this study may be useful to policymakers and stock market investors. Recognizing the limitations of the data utilized in this study, more research can be done using a larger sample size and more sophisticated technique. Additionally, utilizing primary data, a behavioural research of investors’ reactions to market reactions throughout the pandemic era may be carried out.